Integration of strategic HRM policies in organizational decision-making to enhance performance and long-term sustainability - Widowati, Dyah; Wahab, Abd.; Idrus, Syech; Sadikin, Abdurrahman; Hadi, Moch Aminudin (Indonesian Indovisi Institute, 2026)
This study examines the integration of Strategic HRM policies in organizational decision-making to enhance performance and ensure long-term sustainability. The research addresses the challenge organizations face in aligning HRM practices with strategic goals, which often leads to operational inefficiencies and missed opportunities. The objective is to explore how effective HRM integration influences decision-making processes and contributes to improved organizational outcomes. Using a library research methodology, data was gathered from relevant literature, including academic books, journals, and research reports. The findings reveal that organizations that integrate HRM into decision-making processes tend to achieve better performance, higher employee engagement, and greater sustainability. However, barriers such as resistance to change, lack of leadership support, and structural issues need to be overcome. The study concludes that HRM integration plays a vital role in organizational success, with the potential to drive long-term competitiveness and resilience.